From Ritual Theory To a Spiritual Biology: Prayer and the Activation of Chakras-Hormones in Human Metabolism - Aris Widodo; Dwi Purbowati (Universitas Islam Negeri Mataram, 2022)
Prayer as one of the essentials of human beings as